1979
DOI: 10.2135/cropsci1979.0011183x001900030015x
|View full text |Cite
|
Sign up to set email alerts
|

Response to Mass Selection for Flowering Time in Meadowfoam1

Abstract: A population of meadowfoam (Limnanthes alba Hartw.) was subiected to mass selection for early and late flowering time for two generations. Selected plant bulks were grown in C1 and C2 generations along with the original population (C0). The responses to selection were significant in both generations. Heritability estimates assuming random mating, ranged from 0.24 to 0.73. Flowering time involved phenotypic assortative mating, which was discussed for its effects on the herltability estimates and population stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Initial population surveys for allozyme variation indicated that Indian amaranths were largely monomorphie G*^' -^ ^^ ^1-J980). However, gram amaranth species are facultatively allogamous; estimates of outcrossing rates at Davis, California indicated a mixed mating system for A. cruentus (JAIN et al 1982), and our observations from germplasm nurseries and variety trials at Davis suggested ubiquitous polymorphism for inflorescenee color and large variation in many agronomic traits.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Initial population surveys for allozyme variation indicated that Indian amaranths were largely monomorphie G*^' -^ ^^ ^1-J980). However, gram amaranth species are facultatively allogamous; estimates of outcrossing rates at Davis, California indicated a mixed mating system for A. cruentus (JAIN et al 1982), and our observations from germplasm nurseries and variety trials at Davis suggested ubiquitous polymorphism for inflorescenee color and large variation in many agronomic traits.…”
mentioning
confidence: 58%
“…Variation in quantitative characters was observed among-and-within landrace populations of South and Central American landraces (HAUPTLI and JAIN 1984) and of Indian landraces (VAIUYA and JAIN, ms. submitted), largely based on between family component, interpreted as largely the additive and additive X additive gene action. Mass selection has been used in wild rice [Zizanla aquatica) (E\'ERETT and STUGKER 1983)., Limnanthes (JAIN 1979), Crambe (MEIER and LESSMAN 1973), and several forage species. The objective of this study was to determine, by examining the response in a mass selection experiment, the extent of quantitative genetic variation in two amaranth populations.…”
mentioning
confidence: 99%
“…The evolutionary response depends not only on the direction and intensity of selection, but also on genetic variability for this trait and other genetically correlated traits. Though a genetic basis for flowering time has been demonstrated in many plant species (e.g., Lolium temulentum -Cooper, 1959;Melandrium album and M. rubrum-Lawrence, 1963;Mimulus cardinalis and M. lewisii-Hiesey, Nobs, and Bjorkman, 1971; Glycine max- Lin and Nelson, 1988;Senecio integrifolius-Widen, 1991a) and flowering time has been modified by artificial selection in Zea mays (Paterniani, 1969;Troyer and Larkin, 1985), Limnanthes alba (Jain, 1979), Plectris brachystemon and P. congesta (Carey, 1983), nothing is known about the genetic basis for the individual variation observed in Phlox's flowering time. It is suggestive that little or no heritability has been found in Phlox for a germination trait (a correlated phenology) under similar strong, directional selection (Kelly and Levin, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…1977; Schmitt, 1983;Marquis, 1988;Lotz, 1990;Widen, 1991a), (5) herbivore attack (e.g., Augspurger, 1981;Zimmerman and Gross, 1983;English-Loeb and Karban, 1992), or (6) plant density (e.g., Augspurger, 1981;Schmitt, 1983). Individual differences in the timing of flowering also may be genetically determined (e.g., Cooper, 1959;Lawrence, 1963;Hiesey, Nobs, and Bjorkman, 1971;Jones, 1971;Westerman, 1971;McIntyre and Best, 1978;Jain, 1979;Carey, 1983;Troyer and Larkin, 1985;Widen, 1991a;and reviewed in Murfet, 1977). When the timing of flowering is genetically determined, differences in the fitness of plants that begin to flower at different dates can be directly related to their genotype.…”
mentioning
confidence: 99%
“…Agronomic studies have investigated growth parameters such as germination conditions, cultivation, fertilizers, and harvesting methods to optimize seed and oil yields (Jain 1979;Franz and Jolliff 1989;Jahns and Jolliff 1990;Fiez et al 1991).…”
Section: Morphology Importance and Distributionmentioning
confidence: 99%